محاكم القضاء التجاري في المملكة العربية السعودية = Commercial judicial courts in the Kingdom Of Saudi Arabia - Laeba, Muhammad; Negasi, Mohamed Ibrahim; Alkhulaidi, Maher Hasan; Heriz, Mohammad Salem (Faculty Sharia and Law, Al-Azhar University, 2020)
تجسد التجارة العمق الاقتصادي سواء للدول أو للمجتمعات أو للأفراد، فمن الأهمية بمكان أن تأخذ الدول بإصدار العديد من الأنظمة والتشريعات المنظمة للعلاقة التجارية على مستوى الداخلي للدولة للأفراد فيما بينهم، أو بين المجتمع الواحد، أو على المستوى الخارجي بوضع الأنظمة المتعلقة بالتجارة الإقليمية، وطبيعة للتباين والاختلافات التي ستقع بين الفراد بسبب العلاقة التجارية ستنشأ خصومات متعددة، ومطالبات لحقوق غير مستوفاة، فكان لا بد من إنشاء جهة تفصل بين الخصوم، وهو القضاء متمثل في المحاكم. ومن بين تلك الدول المملكة العربية السعودية التي أخذت بالعناية بهذا الجانب منذ عهد المؤسس جلالة الملك عبد العزيز -طيب الله ثراه – فقامت بسن الأنظمة والتعليمات المتعلقة بالتجارة والاقتصاد، وقد صاحب ذلك تطور في الجهات القضائية التي تتولى الفصل في الخصومة القائمة على أساس العلاقة التجارية، وقد مر هذا التطور في المملكة بمراحل عدة. وبالأهمية بمكان الإشارة إلي تلك المراحل التي مر بها القضاء التجاري، ومع ما صاحبه من تطور في سن الأنظمة والتعليمات التي تتسم بالمرونة والأصالة، ومن المهم التطرق إلى المنظومة العدلية، وما حصل فيها من تطور في الأنظمة العدلية، والتشكيل القضائي للمحاكم عامة، - المتعلقة بالقضاء التجاري- سواء المحكمة العليا، أو محاكم الاستئناف، أو محاكم الدرجة الأولى، والتوزيع الداخلي للدعاوى، وتناولنا القواعد والأحكام التي يجب مراعاتها في الخصومة أمام تلك المحاكم، ومن أهم تلك القواعد والأحكام المتعلقة بأوجه الاختصاص النوعي، والاختصاص الولائي، والاختصاص القيمي أمام المحاكم التجارية، والضوابط التنظيمية للنظر في القضايا من قبل دوائر الدرجة الأولى التجارية، والدوائر الاستئنافية التجارية، والدوائر التجارية في المحكمة التجارية، وفقا لنظام القضاء لعام 1428ه، ونظام المرافعات الشرعية لعام1435ه، والتطرق أيضاً إلى مشروع نظام المحاكم التجارية وإجراءاتها وما فيه من قواعد وأحكام وأوجه التباين مع ما في نظامي القضاء والمرافعات الشرعية. *************************************************************************** Commerce has the highest depth in economy, and it is highly important either to states, societies, or to individuals. It is extremely necessary for countries to adopt the issuance of many regulations and legislations to establish the commercial relation at the internal level of the state for all individuals and levels, between one community and anther, or at the external level by establishing regional regulation trade. Due to different individuals’ perspective in commercial relationship aspect, multiple conflicts are expected; and some might claim that their rights are unfulfilled. Therefore, it is extremely necessary to have courts to represents the judiciary to separate the opponents. Among these countries is The Kingdom of Saudi Arabia. Since the majesty King Abdulaziz- may GOD rest his soul- he has enacted regulations and instructions related to trade and economic, the kingdom has gone through several changes. This has been accompanied by the development in the judicial authorities that decide the litigation based on the commercial relationship. Therefore, it is important to state that the commercial judiciary development stages, regulation, and instructions known with its flexibility and authenticity. Also, it is crucial to address that the justice system and how it has evolved in the judicial system either related to the general judicial formation of courts, to the supreme court, to the judiciary commercial, or to the appeals courts. Furthermore, dealing with rules and provisions must be considered in the litigation in front of those courts. Those rules and provision were discussed in the specific competencies, state jurisdiction, valuable jurisdiction, and the regulatory controls for hearing cases the first-degree commercial circles. Moreover, it was addressed also in 1428 AH, the judicial system; in 1435 AH, the Low of Legal Procedures, and the commercial courts system and its procedures; rules, provision; and its contrasts with what is in the legal system.